The Reaper : autobiography of one of the deadliest Special Ops snipers - Irving, Nicholas (St. Martin's Press, 2015)
A memoir by a Special Operations Direct Action Sniper traces his extraordinary career during the War on Terror, which was marked by his record-setting deployment to Afghanistan and his face-off against an enemy sniper known only as The Chechnian.